PENGARUH SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU - Afriyanli, Hana Khairi; Sabandi, Ahmad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This paper examined the influence of principal supervision on teacher performance at Vocational High school 2 Padang. This is a correlational research. The population is 76 teachers and research sample is 43 teachers that are taken by propotional stratified random sampling. The instrument was questionnaire with Likert scale models that had been tested forits validity and reliability. The data were analyzed by simple linear regression. The results showed that the influence of principal supervision on teacher performance at Vocational School (SMKN) 2 in Padang was significant.